Haemoptysis: An unusual initial presentation of achalasia cardia - Tapadar, Sumit Roy; Deb, Jaydip; Dhua, Aparup; Bhattacharya, Soumya; Bairagya, Tapan Das; Biswas, Uttam (Asian Journal of Medical Sciences, 2014)
A 31 year old male presented with haemoptysis, fever and cough. Chest Radiography showed patchy consolidation with breakdown in lower lobe of left lung. Further evaluation revealed the presence of achalasia cardia that resulted haemoptysis due to aspiration pneumonia. This report highlights the uncommon initial presentation of achalasia cardia in the form of haemoptysis in a previously asymptomatic individual. Although haemoptysis occurs commonly due to pulmonary disorders, it may also be an initial symptom of some rare nonpulmonary disorder. Thorough workup with strict vigilance is extremely important to elicit that type of rare aetiology. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10800 Asian Journal of Medical Sciences Vol.6(1) 2015 103-105